The analysis of protecting cultural heritage in armed conflicts. Case of the Russian-Ukraine War - Kudzai Cathrine BINGISAI (Analele Universităţii din Oradea. Relaţii Internaţionale şi Studii Europene)
The current study sought to contribute to the discussions relating to the destruction of cultural heritage in armed conflicts. The relationship between cultural heritage and national identity cannot be separated. The 21st century particularly 2022 has experienced the most violent and radical Russian-Ukraine war from which the spillover effects go beyond geographical borders. The study argues that at the expense of Russia's geopolitical interests, the destruction of cultural heritage is a global protection crisis. By using secondary data sources, this study sought to analyse the challenges of protecting cultural heritage during armed conflicts. The findings present that cultural heritage, both tangible and intangible is an important representation of national identity and promotes cultural diversity. The Russian-Ukraine war has witnessed the destruction of heritage sites, churches and monuments in Ukraine. From a comprehensive point of view, the study presents that regional and international organizations should establish effective efforts and rethinking for the preservation of cultural heritage. The paper argues that technological advancement has also complicated the protection of cultural heritage in global politics thereby threatening the achievement of sustainable development goals.